Pengaruh Promosi, Mutasi Dan Demosi Terhadap Kinerja Pegawai Di Lingkungan Universitas Pembangunan Panca Budi Medan - Ikhah Malikhah; Geby Citra Ananda (Economics, Business and Management Science Journal, 2021)
The purpose of this study is to analyze the extent to which promotion, transfer and demotion affect employee performance at Universitas Pembangunan Panca Budi Medan and to compare the theory that the author has learned with practice in the field. The author examines by collecting various data using library research, structured questionnaires as an instrument to obtain quantitative data with a Likert scale system distributed to 100 respondents. Then the data is processed and analyzed using multiple regression analysis techniques (Multiple Regression) through validity, reliability and classical assumption tests. From the results of the study, it is known that promotion, transfer and demotion simultaneously have a significant effect on employee performance at the Universitas Pembangunan Panca Budi Medan. For the variables of promotion issues, transfer issues and demotion issues, there is a partial influence on employee performance, so it is concluded that demotion dominantly affects employee performance in the Universitas Pembangunan Panca Budi Medan.